Interplay of Toll-Like Receptor 9, Myeloid Cells, and Deubiquitinase A20 in Periodontal Inflammation - Crump, Katie E. (Infect Immun, 2016)
Toll-like receptor 9 (TLR9)-deficient (TLR9(−/−)) mice are resistant to periodontitis, a disease characterized by a dysbiotic microbiota and deregulated immune response and resulting in tooth loss and various systemic conditions. However, the mechanisms and biological pathways by which TLR9 instigates periodontal inflammation are yet to be identified. In a ligature-induced model of periodontitis, we demonstrate that TLR9(−/−) mice exhibited significantly less alveolar bone loss than their wild-type (WT) counterparts. Consistent with the disease phenotype, gingival tissues showed significantly more inflammatory cell infiltration in the WT ligated but not in the TLR9(−/−) ligated mice compared to the unligated controls. The peritoneal infection model using Porphyromonas gingivalis, a keystone pathogen for periodontitis, revealed reduced neutrophils in TLR9(−/−) mice on day 1 postinfection compared to the levels in WT mice. Transcriptomics analyses showed increased expression of A20 (tumor necrosis factor alpha [TNF-α]-induced protein 3 [TNFAIP3]), an inhibitor of the NF-κB pathway and a negative regulator of TLR signaling, in ligated TLR9(−/−) mouse gingival tissues compared to its expression in the WT. Ex vivo, TLR9(−/−) bone marrow-derived macrophages produced more A20 than WT cells following P. gingivalis challenge. Clinically, A20 was modestly upregulated in human gingival tissue specimens from chronic periodontitis patients, further confirming the biological relevance of A20 in periodontal inflammation. We conclude that TLR9 modulates periodontal disease progression at both the cellular and molecular level and identify A20 as a novel downstream signaling molecule in the course of periodontal inflammation. Understanding the regulation of the TLR9 signaling pathway and the involvement of A20 as a limiting factor of inflammation will uncover alternative therapeutic targets to treat periodontitis and other chronic inflammatory diseases.